2008
DOI: 10.1002/cne.21747
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of NMDA receptor subunit NR3B in selected structures in the rat forebrain, cerebellum, and lumbar spinal cord

Abstract: N-methyl-D-aspartate (NMDA) receptors have been implicated in many neurological disorders. Although NMDA receptors are best known for their high calcium permeability, the recently discovered NR3 subunits, NR3A and NR3B, have been shown to reduce the calcium permeability of the NMDA receptor. Thus, NR3 subunits may be important players in modulating synaptic plasticity in neurons. Although NR3B expression in the rodent and human brain has been studied, little is known about its distribution in different cell ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 67 publications
4
55
0
Order By: Relevance
“…20 The anatomical distribution of the three known subunits of the NMDA receptor, NR1, NR2, and NR3, seems insufficiently specific to be closely correlated with distinct clinical symptoms. [21][22][23] In addition to paroxysmal movements, constant motor agitation was present in all individuals. R, right; L, left; P, partial; G, generalization; SE, status epilepticus; C, complex; TC, tonic-clonic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 The anatomical distribution of the three known subunits of the NMDA receptor, NR1, NR2, and NR3, seems insufficiently specific to be closely correlated with distinct clinical symptoms. [21][22][23] In addition to paroxysmal movements, constant motor agitation was present in all individuals. R, right; L, left; P, partial; G, generalization; SE, status epilepticus; C, complex; TC, tonic-clonic.…”
Section: Discussionmentioning
confidence: 99%
“…20 The anatomical distribution of the three known subunits of the NMDA receptor, NR1, NR2, and NR3, seems insufficiently specific to be closely correlated with distinct clinical symptoms. [21][22][23] …”
mentioning
confidence: 99%
“…However, recent investigations indicate a more widespread localization of NR3B, including its expression in cortex, cerebellum and hippocampus in the adult rat CNS [15,32]. In the human forebrain, NR3B mRNA is expressed in the CA1 to CA4 regions and dentate gyrus of the hippocampus [23].…”
Section: Expression Profile Of the Nr3 Subunitsmentioning
confidence: 98%
“…NR3B protein was found to be expressed in all of the substructures of the hippocampus (CA1, CA3, dentate gyrus); the various layers of the cerebral cortex, projection neurons, and interneurons of the striatum; different cell types of the cerebellum; and motor neurons of the spinal cord (Wee et al, 2008). In the cerebral cortex, NR3B immunoreactivity was detected in all of the layers.…”
Section: Nmda Receptor Nr3 Subunitsmentioning
confidence: 95%
“…On the other hand, NR3B expression was initially shown to be restricted to a few prominent regions such as the spinal cord, brain stem, cerebellum, and hippocampus (Nishi et al, 2001;Matsuda et al, 2002;Bendel et al, 2005). Recently, Wee et al (2008) reported a comprehensive study to systematically compare NR3B protein and NR1 localization across major brain regions. The study used immunolabeling with specific NR3B antibody on rat brain slices and revealed that there is a more widespread distribution of NR3B protein in the forebrain (hippocampus, cerebral cortex, caudoputamen, and nucleus accumbens), cerebellum, and lumbar sections of the spinal cord.…”
Section: Nmda Receptor Nr3 Subunitsmentioning
confidence: 99%